MONITORING INFORMATION SYSTEM FOR CHILDHOOD NUTRITION STATUS AT SEA SINDANG CIREBON HEALTH CENTER APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Rahayuwati Rahayuwati; Cut Asiana Germawaty, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Perform measurements of nutritional status on one age group is one method of assessing nutritional status of the population. In Cirebon District has conducted periodic measurement of body weight at toddler groups to obtain information on nutritional status from time to time up to the district level. Nutritional status information is very useful to obtain a picture of nutrition problems of population size which in turn is used  to support regional planning a regional program.   PHC as one important element in monitoring the nutritional status of children at district level. However, generally in the center area of Cirebon toddlers data processing system that starts from the input, the determination of nutritional status, and storage is still done manually. This happened also in the PHC village, Cirebon Sea. Given the number of children so much, then the manual method is less effective and efficient, especially in the process of determining the nutritional status of the filing and storage cabinets that need a place wide enough, and toddler data search process that requires a relatively long time. Therefore, the author wants to facilitate that process by creating a computerized information system that can provide solutions to those problems.